2019
DOI: 10.1016/j.fertnstert.2018.11.047
|View full text |Cite|
|
Sign up to set email alerts
|

Corifollitropin alfa for ovarian stimulation in in vitro fertilization: a systematic review and meta-analysis of randomized controlled trials

Abstract: Objective: To evaluate the effectiveness of corifollitropin alfa in improving the success of IVF. Design: Systematic review and meta-analysis. Setting: Not applicable. Patient(s): Infertile women undergoing conventional IVF or intracytoplasmic sperm injection (ICSI). Intervention(s): Randomized controlled trials (RCTs) of infertile women undergoing a single IVF/ICSI cycle with either corifollitropin alfa or a conventional ovarian stimulation protocol based on daily injections. The review protocol was registere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…The authors did not find any difference in the rates of live birth, overall pregnancy, clinical pregnancy, pregnancy wastage (miscarriage), multiple gestation, cycle cancelation, ovarian hyperstimulation syndrome (OHSS), or ectopic pregnancy (1). Therefore, the authors correctly concluded that corifollitropin-a is as effective as recombinant follicle-stimulating hormone (FSH) for IVF in normal or low responders (1). Furthermore, the number of the total retrieved oocytes, metaphase 2 (MII) oocytes, and generated embryos were statistically significantly higher in the patients treated with corifollitropin-a compared with the group receiving daily FSH injections (1).…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…The authors did not find any difference in the rates of live birth, overall pregnancy, clinical pregnancy, pregnancy wastage (miscarriage), multiple gestation, cycle cancelation, ovarian hyperstimulation syndrome (OHSS), or ectopic pregnancy (1). Therefore, the authors correctly concluded that corifollitropin-a is as effective as recombinant follicle-stimulating hormone (FSH) for IVF in normal or low responders (1). Furthermore, the number of the total retrieved oocytes, metaphase 2 (MII) oocytes, and generated embryos were statistically significantly higher in the patients treated with corifollitropin-a compared with the group receiving daily FSH injections (1).…”
mentioning
confidence: 91%
“…Although after 40 years the practice of in vitro fertilization (IVF) has come of age, controlled ovarian stimulation for assisted reproductive technology (ART) continues to undergo changes to improve clinical outcomes and make the overall treatment experience less expensive and more comfortable, simple, and user-friendly. In this issue of Fertility and Sterility, Cozzolino et al (1) summarize randomized controlled trials (RCTs) with infertile women who underwent a single cycle of IVF with intracytoplasmic sperm injection (ICSI) cycle using either corifollitropin-a or a conventional ovarian stimulation protocol based on daily injections (1). The authors correctly explain that the use of daily injections for infertility treatment may augment the patients' anxiety due to the possibility of unintentional mistakes.…”
mentioning
confidence: 99%
See 3 more Smart Citations